Pengetahuan dan Dukungan Suami tentang Pijat Oksitosin Minyak Sereh di PMB Muzilatulnisma - Jayanti, Ova; Nurita, Suci Rahmani; Patriani, Sirly (Jurnal Akademika Baiturrahim Jambi, 2024)
Oxytocin massage is a massage along the spine (vertebrae) and is an effort to stimulate the hormone oxytocin after giving birth. Lemongrass oil can provide a relaxing effect on breastfeeding mothers and prevent postpartum blues. However, not many mothers know the benefits of oxytocin massage with lemongrass oil. Oxytocin massage cannot be done by mothers independently, therefore it requires husband's support. This study aims to determine the description of mothers' knowledge and husband's support in performing lemongrass oil oxytocin massage. The research method used a cross-sectional design with a sample of 45 breastfeeding mothers at PMB Muzilatulnisma Jambi. This study was conducted by distributing questionnaires, data were analyzed univariately. The results of the study showed that 82.2% of respondents were aged 20-35 years, their last education was high school to undergraduate, 75.5% were housewives, 84.4% had good knowledge, 15.6% had poor knowledge. Husband's support was good at 73.3% and husband's support was poor at 26.7%. The conclusion of this study is that the majority of mothers have good knowledge and good husband support. It is recommended that husbands increase their support for their wives during the breastfeeding process in order to achieve exclusive breastfeeding for 9 months.